A very rare case of polysplenia syndrome with congenital diffuse pulmonary arteriovenous fistulas - Gürses, Dolunay; Ulger, Zülal; Levent, Ertürk; Ozyürek, A Ruhi (The Turkish Journal of Pediatrics, 2006)
A five-year-old girl patient was admitted with cyanosis and dyspnea, which started from birth. She had small telangiectatic lesions on her face and cerebral arteriovenous malformation, but no family history of hereditary hemorrhagic telangiectasia. Contrast echocardiography and pulmonary angiography demonstrated diffuse pulmonary arteriovenous fistulas. The patient was diagnosed as polysplenia syndrome characterized with left atrial isomerism, interrupted inferior vena cava, azygous continuation to the superior vena cava, and hepatic veins draining to the right atrium. In contrast to the other polysplenia syndrome cases, in this patient, pulmonary arteriovenous fistulas were not associated with cavopulmonary anastomoses or liver disease.